A Fair and Privacy-preserving Reservation Scheme for Charging Electric Vehicles - Rabieh, Khaled; Aydogan, Ahmet Furkan (Ieee, 2019)
Enormous benefits are expected from Electric Vehicle (EV) which is a promising alternative to replace traditional gasoline car. However, the EV's cruising range is much shorter than the range offered by gasoline cars. Congestion at the charging stations is expected not only because of the frequent charging demands of EVs, but for the long time of charging batteries as well. In this paper, we propose a privacy-aware and fair reservation scheme for EVs charging scenarios. The drivers submit their reservation requests to the charging stations anonymously to protect their location privacy. To achieve fairness, a selfish driver should not be able to submit/authenticate many reservation requests to fill the charging queue for his own benefit. The EVs use an efficient anonymous credentials from bilinear pairings for anonymous authentication with the charging station to protect their privacy and K-times anonymous authentication to restrict a selfish driver from submitting many reservation request. Our evaluations show that the proposed scheme can efficiently preserve the drivers' privacy, secure the communication and achieve fairness with low communication and computation overhead.
International Symposium on Networks, Computers and Communications (ISNCC) -- JUN 18-20, 2019 -- Istanbul, TURKEY
Keywords: EV charging; anonymous authentication; privacy preserving; electric vehicles; and fair services